Design, synthesis, and molecular docking studies of novel pomalidomide-based PROTACs as potential anti-cancer agents targeting EGFRWT and EGFRT790M - Moustafa O. Aboelez; Amany Belal; Guangya Xiang; Xiang Ma (Journal of Enzyme Inhibition and Medicinal Chemistry)
A new class of EGFR PROTACs based on pomalidomide was developed, synthesised, and tested for their cytotoxic activity against a panel of human cancer cells. Compounds 15–21 were showed to be more effective against the four tested cell lines than erlotinib. In particular, compound 16 was found to be the most potent counterpart as it was 5.55, 4.34, 5.04, and 7.18 times more active than erlotinib against MCF-7, HepG-2, HCT-116, and A549 cells, respectively. Compound 15 was revealed to be more active than doxorubicin against the four tested cell lines. Furthermore, the most potent cytotoxic compounds were studied further for their kinase inhibitory effects against EGFRWT and EGFRT790M using HTRF test. Compound 16 showed to be the most effective against both kinds of EGFR, with IC50 values of 0.10 and 4.02 µM, respectively. Compound 16 could effectively degrade EGFR protein through ubiquitination (Dmax = 96%) at 72 h in the tested cells.